From varices to venous ulceration: the story of chronic venous disease described by metalloproteinases. Issue 1 (15th March 2016) - Serra, Raffaele; Gallelli, Luca; Butrico, Lucia; Buffone, Gianluca; Caliò, Francesco G; De Caridi, Giovanni; Massara, Mafalda; Barbetta, Andrea; Amato, Bruno; Labonia, Miriam; Mimmi, Selena; Iaccino, Enrico; et al.
Abstract: Chronic venous disease (CVD) and its most frightening complication, chronic venous ulceration (CVU), represent an important socioeconomic burden in the western world. Metalloproteinases have been identified in the pathogenesis of several vascular diseases such as venous problems. The aim of this study was to evaluate a broad range of metalloproteinases, such as matrix metalloproteinases (MMPs), ADAMs (a disintegrin and metalloproteinases) and ADAMTSs (a disintegrin and metalloproteinases with thrombospondin motifs) and their inhibitors, tissue inhibitor of metalloproteinases (TIMPs) and a related protein, neutrophil gelatinase‐associated lipocalin (NGAL), in patients with CVD in order to correlate their serum levels with each stage of the disease. We performed a multicenter open‐label study that comprised the enrolment of 541 patients with CVD of clinical stages C1–C6, (178 males, 363 females; mean age 57·29, median age 53·72, age range 29–81); 29 subjects without CVD were included in this study (9 males and 20 females; mean age 54·44, median age 50, age range 28–84) as the control group. Enzyme‐linked immunosorbent assay (ELISA) was performed for measuring serum levels of proteases and related proteins. The study found that the serum elevation of MMP‐2, ADAMTS‐1 and ADAMTS‐7 appeared to be correlated with the initial stages of CVD, whereas the serum elevation of MMP‐1, MMP‐8, MMP‐9, NGAL, ADAM‐10, ADAM‐17 and ADAMTS‐4 was particularly involved in skin change complications. This study showed that each stage of CVD may be described by particular patterns of metalloproteinases, and this may have therapeutic implications in discovering new targets and new drugs for the treatment of CVD.